Effects of nano-Rhodiola rosea combined with treadmill exercise on anti-exercise fatigue in rats - Wang, Jibing; Zhang, Guoyan; Wang, Duona; Yan, Yuanyuan; Yang, Qin (Frontiers in Nutrition, 2024)
Objective To explore the potential strategies and mechanisms for enhancing the bioavailability of Rhodiola rosea. Methods 36 Sprague–Dawley rats (8-weeks-old) were randomly assigned to six groups (n = 6 per group). Groups I and II received nano-dose forms of R. rosea, groups III and IV received normal dose form of R. rosea, and groups V and VI served as distilled water control groups. Groups II, IV, and VI were combined with moderate -intensity treadmill exercise. Each group received a daily gavage with 0.5 mL of nano -R. rosea solution (0.01 mg/mL), normal R. rosea solution, and distilled water. All rats were subjected to exhaustive swimming after 4 weeks. Outcome measures include GSH-px activity, T-AOC activity, MDA content, hepatic glycogen content, and T-SOD activity. Results For plasma MDA content, group I was lower than group III (p < 0.01) and group V (p < 0.01), group II was lower than group III (p < 0.01), group VI was higher than group II (p < 0.05) and group IV (p < 0.05). For plasma T-AOC activity, group II was higher than group VI (p < 0.01). For plasma GSH-px activity, group I was lower than group IV (p < 0.05), groups II, III, and IV were higher than group V (p < 0.05), and group V was lower than that of group VI (p < 0.05). For T-SOD activity of quadriceps muscle, groups I and III were higher than that in group V (p < 0.05). Conclusion R. rosea has a positive effect on anti-exercise fatigue in rats, with the nano-dosage form of R. rosea showing more significant efficacy than the normal form especially combined with aerobic exercise.